2022
DOI: 10.1039/d2fo01283a
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofLycium barbarumarabinogalactan on the fecal metabolome in a DSS-induced chronic colitis mouse model

Abstract: Gut microbes and untargeted/targeted metabolomics were combined to comprehensively understand the therapeutic effect and the underlying mechanism of Lycium barbarum arabinogalactan (LBP-3) in DSS-induced colitis mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 72 publications
2
10
0
Order By: Relevance
“…31 In addition, a recent study has demonstrated that the content of tryptophan in mice with DSS-induced colitis was lower than normal. 24,32 The present study suggests that tryptophan was positive with IL-10 expression. Deprivation of tryptophan would also induce the progression and exacerbation of colonic inflammation in patients.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…31 In addition, a recent study has demonstrated that the content of tryptophan in mice with DSS-induced colitis was lower than normal. 24,32 The present study suggests that tryptophan was positive with IL-10 expression. Deprivation of tryptophan would also induce the progression and exacerbation of colonic inflammation in patients.…”
Section: Discussionsupporting
confidence: 57%
“…5 The gut microbiota could interact with polysaccharides to produce metabolites that have an important role in maintaining intestinal homeostasis. 4,24 However, the metabolic changes in gut microbiota regulated by the supplementation of ANP are still unknown. Therefore,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, our latest research showed that arabinogalactan-type LBP-3 could reverse the levels of certain specific amino acids (e.g., tryptophan, phenylalanine, lysine, glutamine, homoserine, and leucine) and organic acids, (e.g., kynurenine, 2-isopropylmalic acid, ascorbic acid, gluconic acid, ( S )-2-hydroxyglutarate, and taurine) disturbed by DSS induction [ 104 ]. Moreover, pathway analysis indicated that the pentose phosphate pathway, phenylalanine, tyrosine and tryptophan biosynthesis, and phenylalanine metabolism were also altered by LBP-3 [ 104 ]. Additionally, LPS is also considered an intestinal bacterial metabolite, and its level was dramatically reduced by LBPs in HFD/streptozotocin (STZ)-induced diabetes in rats and mice [ 101 , 105 ].…”
Section: Impact Of Lbps On Gut Microbiota and Its Metabolitesmentioning
confidence: 99%